Describing Weight Loss Attempts and Physical Activity Among Individuals With TBI Prior to Participation in a Weight-Loss Program. Issue 1 (January 2018) - Driver, Simon; Reynolds, Megan; Douglas, Megan; Bennett, Monica
Abstract : Objective: Describe (1) weight loss history, (2) perceptions about lifestyle changes, and (3) physical activity among a sample of individuals with traumatic brain injury prior to a 12-month lifestyle change program. Setting: Community-based. Participants: Individuals enrolled in a lifestyle change program, 6 months or more post–traumatic brain injury, body mass index of 25 or greater, 18 to 64 years of age, with physician's clearance to participate. Design: Convenience sample. Main Measures: Self-report data were collected before beginning the lifestyle change program including descriptive, weight loss history and physical activity behavior using the Modifiable Activity Questionnaire. Results: The final sample included 22 participants ( M age = 46 years) injured a median of 8 years ago. Mean weight was 208.5 lb (SD = 40.2), with average body mass index of 31.84 (SD = 4.4). Since injury, 72.7% reported prior weight loss attempts, with 50% gaining 10 lb or more. All participants indicated high motivation for lifestyle changes. Perceived benefits included feeling better, improving overall health, and increased energy. Barriers included physical health complications. Types of physical activity completed included walking (68%, 180 min/mo) and swimming (32%, 79 min/mo). Conclusion: Results indicate that many individuals gained weight since injury and attempted weight loss, demonstrating a need for evidence-based lifestyle interventions. Future research is needed to determine whether individuals with traumatic brain injury are able to achieve and maintain weigh loss through intervention.